Senegalese Women Remake Their Culture - Easton, Peter (World Bank, Washington, DC, 2012)
In 1995, female literacy countrywide in Senegal was just over half of the rate for men, and the discrepancy was greater in rural areas. TOSTAN, literally means "breaking out of the egg" in Wolof, the language spoken by the majority of Senegal's people and is among a number of innovative and rural development and women's education initiatives that are addressing the problem at its sources. It offers an 18-month learning program that combines basic education and national languages with practical development issues, and provides rural people with the resources to improve their standard of living while fostering increased confidence in their way of life. Its popularity among rural women participants broke all records. Shortly after completing their training, the women of Malicounda utilized the program to address the custom of female circumcision. This note discusses elements that contribute to TOSTAN's successful impact in education and sustainable development.